2021
DOI: 10.29244/avi.9.3.215-222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi Kecacingan pada Anjing dan Kucing di Klinik Smilevet Kelapa Gading Periode Januari 2020 - Januari 2021

Abstract: Anjing dan kucing merupakan hewan yang hidup berdampingan dengan manusia sebagai hewan peliharaan. Infeksi parasit cacing merupakan masalah yang umum pada hewan peliharaan namun data tentang prevalensi kejadian kecacingan di Indonesia masih sedikit. Penelitian ini bertujuan untuk mengetahui prevalensi  dan faktor risiko kecacingan pada anjing dan kucing serta tindakan preventif untuk mencegah infeksi parasit cacing. Pengambilan data dilakukan dengan merekap rekam medik yang ada di klinik Smilevet Kelapa Gading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The percentage of nematodiasis cases in pet cats in Yogyakarta from April to December 2022 was higher than that reported in the Smilevet clinic in Jakarta for one year (January 2020-January 2021), namely 1.09% (Natasya et al 2021). Toxocara and Ancylostoma were the main gastrointestinal parasites that infected the pet cats.…”
Section: Discussionmentioning
confidence: 67%
“…The percentage of nematodiasis cases in pet cats in Yogyakarta from April to December 2022 was higher than that reported in the Smilevet clinic in Jakarta for one year (January 2020-January 2021), namely 1.09% (Natasya et al 2021). Toxocara and Ancylostoma were the main gastrointestinal parasites that infected the pet cats.…”
Section: Discussionmentioning
confidence: 67%
“…Age affects the incidence of infection at the level of protozoa. The incidence of protozoan infection in young cats is higher than in old cats [9]. Cats that have been infected usually show clinical symptoms of acute and chronic diarrhea, this is due to the activity of protozoa in the digestive tract to live and reproduce [21].…”
Section: Figure 1 Results Of Observation Infestation Oocyst In Domest...mentioning
confidence: 99%
“…The proportion of helminthiasis in males is 14.70% and females is 15.78%. Another study reported cases of Toxocara canis infection showing no significant effect between sex and cases of Toxocara canis infection (13,19).…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 96%